PERIODICITY OF SOLUTIONS TO LINEAR SYSTEMS OF ORDINARY DIFFERENTIAL EQUATIONS WITH PERTUBATION - Кузишин, Іванна Ярославівна (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The conditions of existence of nontrivial periodic solutions for linear systems with nonlinear perturbation are obtained. A generalization of the Rayleigh problem for differential equations with different orders and number of parameters is given and new classes of differential equations with perturbations on hypersurface which have periodic solutions are found.